2006
DOI: 10.1021/jf052579w
|View full text |Cite
|
Sign up to set email alerts
|

Production of Silkworms with Conjugated Linoleic Acid (CLA) Incorporated into Their Lipids by Dietary CLA

Abstract: Silkworms with conjugated linoleic acid (CLA) incorporated into their lipids (designated CLA silkworms) were produced to enhance the quality of silkworms having a synergistic effect with CLA functions by dietary synthetic CLA. Silkworm larvae were fed fresh mulberry leaves (control diet) until the third instar stage and were then subjected to various levels (0%, 0.1%, 1%, 5%, and 10%) of CLA-sprayed mulberry leaves (designated CLA diet) beginning on the first day of the fourth instar stage and continuing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Egg embryogenesis was not impacted by maternal dietary CLA, which was previously reported in laying hens [21, 22]. Park et al, 2006 observed that silkworms fed on a 10% CLA diet had significantly reduced body weight and food intake compared to control silkworms over the 4 th instar stage [23]. In the common house fly, researchers concluded intake up to 10% CLA had no adverse fitness effects on any stage of the insects evaluated [24].…”
Section: Introductionmentioning
confidence: 70%
“…Egg embryogenesis was not impacted by maternal dietary CLA, which was previously reported in laying hens [21, 22]. Park et al, 2006 observed that silkworms fed on a 10% CLA diet had significantly reduced body weight and food intake compared to control silkworms over the 4 th instar stage [23]. In the common house fly, researchers concluded intake up to 10% CLA had no adverse fitness effects on any stage of the insects evaluated [24].…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, the C/EBP-binding sites predicted in the 5′-flanking region of AccFABP may be involved in the regulation of FABP genes and intermediary metabolism (Bernlohr et al 1997). Recent studies have shown that CLA accumulated in the tissues of houseflies and silkworms after breeding, affecting lipid metabolism (Park et al 2000, 2006). The levels and ratio of DHA and AA could influence development across animal species, and dietary deficiency could cause reproductive failure and reduced growth (Davis-Bruno et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FAs play a role in the transcription of genes that encode proteins involved in lipid metabolism (Duplus et al 2000). Conjugated linoleic acid (CLA), which is a type of FA, has unique effects on lipid metabolism, and also provides several health benefits for humans and insects (Park et al 2006). Docosahexaenoic acid (DHA) and arachidonic acid (AA), which are major FAs of the retina, affect gene expression by regulating the activity and concentration of transcription factors within the nucleus (Saino-Saito et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of DNJ extracted from mulberry suppresses an increase in postprandial blood glucose in humans (Tsuduki et al ., 2009) and the lipid-lowering effects of mulberry water extracts (MME) for 12 weeks on hamsters showed hypolipidemic effects of high fat cholesterol diets with 1 and 2% (MME) (Liu et al ., 2009) . Conjugated linoleic acid (CLA) provides several health benefits for humans as an anticarcinogenic or antiatherosclerogenic agent (Park et al ., 2006) .…”
Section: Introductionmentioning
confidence: 99%
“…Silkworms with conjugated linoleic acid (CLA) incorporated into lipids were produced to enhance the quality of silkworms having a synergistic effect with CLA functions by dietary synthetic CLA (Park et al ., 2006) .…”
Section: Introductionmentioning
confidence: 99%